2003
DOI: 10.1007/s00330-002-1547-3
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy (1H MRS) of human brain tumours: assessment of differences between tumour types and its applicability in brain tumour categorization

Abstract: Our objective was to evaluate the usefulness of proton magnetic resonance spectroscopy ( 1 H MRS) in categorizing brain tumours. In vivo single-voxel 1 H MRS at an echo time of 136 ms was performed in 108 patients with brain neoplasms that included 29 meningiomas (MEN), 15 low-grade astrocytomas (LGA), 12 anaplastic astrocytomas (AA), 25 glioblastomas (GBM) and 27 metastases (MET). Time-domain fitted areas of nine resonances were evaluated in all spectra. Twenty-five additional tumours were prospectively inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(45 citation statements)
references
References 24 publications
2
39
0
4
Order By: Relevance
“…Our results showing that we can differentiate brain tumor types based on the amount of Gly and Myo they contain are in agreement with prior observations (31–33). Indeed, the examined tumor types were characterized by differential relative amounts of Gly and Myo (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showing that we can differentiate brain tumor types based on the amount of Gly and Myo they contain are in agreement with prior observations (31–33). Indeed, the examined tumor types were characterized by differential relative amounts of Gly and Myo (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…A low Gly:Myo ratio also distinguishes MT from other tumors, especially GBM, which had the highest ratio of all tumor types examined in this study. The ability to distinguish high-grade gliomas such as GBM from other tumor types (33), especially MT tumors, is clinically important given that our ability to make this distinction is currently inadequate (35). This distinction was not made successfully in a previous study in which GBM and MT were combined into a single group; the authors concluded that a reliable separation between high-grade brain tumors and metastasized tumors cannot be confidently achieved using single voxel 1 H MRS spectroscopy alone (24–26,35).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Magnetic Resonance Imaging (MRI) is the most used technique for diagnosis and management of brain tumours, providing detailed anatomic information [14,15]. This can be supported by Magnetic Resonance Spectroscopy (MRS) and Spectroscopic Imaging (MRSI), which allow collecting non-invasive biomarkers, that may provide important clues about tumour biology and response to treatment [16,17]. Single voxel (SV) MRS measures the average metabolic information of a tumour [16,17], whereas multivoxel acquisition MRSI provides spatially resolved metabolic information [18][19][20], which may be superimposed to anatomical acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Meningioma should have a distinctive elevation in the resonance peak for alanine, which was not the case for this patient. [22] The presence of a significant NAA peak in the current lesion is evidence against the diagnosis of a meningioma or an abscess. The ratio of Cho/NAA ratio was more suggestive of low-grade growth.…”
Section: Discussionmentioning
confidence: 99%